Diatoms and their role in aquatic ecosystems - Neidoni Dorian-Gabriel (Proceedings of the International Symposium on Analytical and Environmental Problems, 2020)
The present article aimed to determine diversity and abundance of diatoms in the river basin of the Cerna River. In order to achieve the objective, samples were taken from the entire course of the river, from 9 specific points (I, II, III, IV, V, VI, VII, VIII, IX) in spring-summer of 2020. 53 species of diatoms classified in 21 genera were determined.